Climate change and plant diseases (Scientia Agricola, 2008)
Human activities are altering greenhouse gas concentrations in the atmosphere and causing global climate change. In the near future, there will certainly be changes in the Brazilian phytosanitary scenario attributed to global climate change. The impacts of climate change can be positive, negative or neutral, since these changes can decrease, increase or have no impact on diseases, depending on each region or period. These impacts will also be observed on plants and other organisms as well as on other agroecosystem components. However, these impacts are not easily determined, and consequently, specialists from several areas must go beyond their disciplinary boundaries and placing the climate change impacts in a broader context. This review focuses on the discussion of different aspects related to the effects of climate change on plant diseases. On the geographical and temporal distribution of diseases, a historical context is presented and recent studies using data of forecast models of future climate associated with disease simulation models are discussed in order to predict the distribution in future climate scenarios. Predicted future disease scenarios for some crops in Brazil are shown. On the effects of increasing concentrations of atmospheric CO2 and other gases, important aspects are discussed of how diseases change under altered atmospheric gases conditions in the future. The consequences of these changes on the chemical and biological control of plant diseases are also discussed.